Exploring Mindfulness Levels and Islamic Religious Manifestations in Early Adolescence - Cahyo Agung Kurniawan; Nofi Nur Yuhenita; Hijrah Eko Putro (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2026)
This study examines the level of mindfulness among students at SMP Negeri 13 Magelang, describes its manifestations through the lens of Islamic religious values, and identifies factors that influence students’ mindfulness. Using a quantitative descriptive design, the study involved 88 students as research participants. The instrument was an adaptation of the Five Facet Mindfulness Questionnaire (FFMQ), modified to suit adolescents’ developmental characteristics and tested for reliability, yielding a Cronbach’s Alpha coefficient of 0.87. The investigation encompassed five dimensions of mindfulness: Observing, Describing, Acting with Awareness, Non-Judging, and Non-Reacting. Data were analyzed using descriptive statistical techniques, including the computation of means, percentages, and standard deviations. The findings indicate that students’ mindfulness levels fall within the moderate category across all dimensions, suggesting that although students exhibit self-awareness, their attention regulation and emotional management remain suboptimal. From the perspective of Islamic religious values, students’ mindfulness is reflected in the principles of patience, gratitude, trustworthiness, sincerity, reliance on God (tawakal), and open-heartedness. Overall, the results underscore the significant potential of Islamic religious values in fostering mindfulness and enhancing self-awareness, emotional regulation, and psychological well-being among students.